ANALISIS KELOMPOK FAKTOR-FAKTOR KEMISKINAN DAN KESENJANGAN PEREKONOMIAN MENGGUNAKAN ALGORITMA SELF ORGANIZING MAPS (SOM) DI JAWA TENGAH TAHUN 2015 - Siti Hasna Isnaeni (Universitas Muhammadiyah Surakarta, 2018)
The problem of poverty continues to be a major problem throughout Indonesia's history as a State. The distribution of the poor is also uneven in all regions in Indonesia. In the theory of poverty mentioned that the factors that influence the emergence of poverty problems originated from limitations in terms of economic, whether physical capital (income) or human capital. Therefore, poverty reduction target oriented planning is needed, so that the poverty reduction and economic disparity can be achieved by target. This study aims to analyze the factors that affect poverty and economic inequality to know the characteristics by applying data mining algorithms to determine the grouping of poverty and economic disparities in Central Java in 2015. In the grouping of poverty factors, the object of research that will be used are variables affecting poverty and economic disparity.The group analysis used data mining approach with Kansans and Kohonen Self Organizing Maps (SOM) algorithm.The result of analysis based on WCSS graph and cluster number validation is determined by cluster number 5 with Semarang City as cluster 1, Kudus is in cluster 2, cluster 3 contains 5 cities, in cluster 4 containing 6 districts and 22 other districts are in cluster 5. Keywords: Poverty, Economic Gap, Clustering K-means, Self Organizing Maps (SOM),central java.